Characterization of Muffins Reformulated with Chia and Lyophilized Peach Powder in Terms of Some Technological and Sensory Aspects§ - Dasha Mihaylova; Aneta Popova; Zhivka Goranova; Pavlina Doykina; Bogdan Goranov (Food Technology and Biotechnology, 2023)
Research background. There is an increasing interest in foods with added nutritional value. This study presents the opportunity for the reformulation of muffins using chia seeds and lyophilized peach powder in view of the emerging societal challenges regarding unhealthy eating patterns and food intolerances. Experimental approach. Two new formulations were developed to eliminate the use of eggs and alter the flour content and type. Physical characteristics, texture analysis, water activity, microbial load, antioxidant potential and sensory profile aided in the evaluation of the newly developed products. Results and conclusions. The results indicate an inversely proportional relationship between the relative mass of the dough and physical parameters (density, volume and height) of all muffin formulations. The modification of the original recipe compared to the control sample led to decreased baking losses, increased total phenolic content, as well as enhanced nutritional value in terms of fibre content. The addition of chia seeds and peach powder led to positive sensory changes. The alteration of the original recipe resulted in significant effect on the colour, making the muffins darker and less yellow than the control sample. In terms of texture characteristics, the new formulations had a profile close to the control. Novelty and scientific contribution. Recipe reformulation without deteriorating quality attributes is important for the food technology field. Reformulation should comply with the new expectations of the modern consumer. The study targets an approach where new products with enhanced functional characteristics are presented.